Developing a Secure Messaging Platform in Mobile SMS Using Advanced Encryption Standard Concept - Mutua, Veronicah; Mwaura, Andrew (My University, 2014)
Billions of text messages are sent daily through GSM networks sent in plain text format which makes them susceptible to various attacks. With the increasing number of software crackers available for free in the internet, studies have shown SMS continues to suffer from several security vulnerabilities and loopholes. The aim of this project was to develop a secure messaging platform for Java enabled phones to securely send encrypted short messages via the GSM network.. The application was developed in MDIP 2.0 and CDLC 1.1configurations and applied symmetric encryption concepts. The experimental results revealed that the mobile application was able to encrypt, decrypt, send and receive text messages without adding changing the size of the packets.
Keywords: Connected Limited Device Configuration (CLDC), Global System for Mobile Communication (GSM), Mobile Information Device Profile (MIDP), Short Messaging Services (SMS).